2023
DOI: 10.1039/d3ob00286a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, conformational stability and molecular structure of 4-aryl- and 4,5-diaryl-1,8-bis(dimethylamino)naphthalenes

Abstract: 4-Bromo- and 4,5-dibromo-1,8-bis(dimethylamino)naphthalenes were arylated with arylboronic acids under Suzuki reaction conditions to provide 4-aryl- and 4,5-diaryl-1,8-bis(dimethylamino)naphthalenes, respectively. The interaction of 4,5-dibromo-1,8-bis(dimethylamino)naphthalene with pyridin-3-ylboronic acid was accompanied by heterocyclization leading...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…[35] Additionally, the abovementioned "clothespin effect" in the case of 11 leads to the decrease of the basicity of the "proton sponge" moiety: the annulation of the 5-membered cycle to the peri-positions of 1,8bis(dimethylamino)naphthalene leads to the increase of the internitrogen distance. [49,51,52] Indeed, performed quantum chemical calculations (for R = tert-Bu) have demonstrated that formation of form 15 is thermodynamically less favourable than 11 • H + : ΔΔG (11 g • H + !15 g) = + 8.0 kcal/mol (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Additionally, the abovementioned "clothespin effect" in the case of 11 leads to the decrease of the basicity of the "proton sponge" moiety: the annulation of the 5-membered cycle to the peri-positions of 1,8bis(dimethylamino)naphthalene leads to the increase of the internitrogen distance. [49,51,52] Indeed, performed quantum chemical calculations (for R = tert-Bu) have demonstrated that formation of form 15 is thermodynamically less favourable than 11 • H + : ΔΔG (11 g • H + !15 g) = + 8.0 kcal/mol (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…This is rather surprising, since the protonation of "proton sponges" containing a second basic center generally results in the formation of an equilibrating mixture of protonated species with a proton preferably localized in the internitrogen space. [48][49][50] We believe that the selectivity of the protonation of 11 originates from the abovementioned strong conjugation of the 5-NMe 2 group with an aromatic core: the stabilization of form 11' boosts the basicity of the indole nitrogen on the one hand, and prevents the protonation of the non-conjugated NMe 2 group by inducing a positive charge in close proximity, on the other hand (Scheme 5). A similar effect was previously observed in the case of cations 14, where the conjugation of the 1-NMe 2 group with the aromatic system also prevented the protonation of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, the reason for this is the appearance in molecule 8 of a short CH=CH bridge, which enhances in-plane deformations of the entire molecular system [ 29 ]. As a result, the distance between the pyridine nitrogen atoms and, at the same time, the molecular rigidity naturally increase in the series 3 → 5 → 8 (“clothespin” effect) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%